AGE NORMS FOR THE DEVELOPMENT OF BALANCING FUNCTION IN CHILDREN AGED 9-10 YEARS (Scientific journal of the Fergana State University, 2024)
The article presents a discussion of pedagogical experience and the results of taking into account age characteristics and the use of physical education means in the development of the balance function in children 9-10 years old in extracurricular activities of physical education classes.